2019
DOI: 10.1101/839621
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RNA G-quadruplex structures exist and function in vivo

Abstract: 15Guanine-rich sequences are able to form complex RNA structures termed RNA G-quadruplexes in vitro. Because of their high stability, RNA G-quadruplexes are proposed to exist in vivo and are suggested to be associated with important biological relevance. However, there is a lack of direct evidence for RNA G-quadruplex formation in living cells. Therefore, it is unclear whether any purported functions are associated with the specific sequence content or the formation of an RNA 20 G-quadruplex structure. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…G4s are considered to act as molecular switches to regulate gene expression in metazoan cells (Eddy and Maizels, 2006). In plants, a few studies have reported the role of G4 sequences, such as in transport and gene expression (Garg et al, 2016), growth and development (Yang et al, 2020b), hydrolase activity (Cagirici et al, 2021), stress response, energy status, and sugar availability (Yadav et al, 2017). Here, we report their role in N-response or NUE for the first time.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…G4s are considered to act as molecular switches to regulate gene expression in metazoan cells (Eddy and Maizels, 2006). In plants, a few studies have reported the role of G4 sequences, such as in transport and gene expression (Garg et al, 2016), growth and development (Yang et al, 2020b), hydrolase activity (Cagirici et al, 2021), stress response, energy status, and sugar availability (Yadav et al, 2017). Here, we report their role in N-response or NUE for the first time.…”
Section: Discussionmentioning
confidence: 80%
“…But together, they span diverse genotypes, N-forms and growth conditions yielding thousands of DEGs and enabling comprehensive meta-analyses. Identification of co-expressed genes/modules by methods such as WGCNA is one of the ways to distill the essence from all these datasets, but so far this was done only with individual N-responsive transcriptomic datasets in rice (Coneva et al, 2014;Zhang et al, 2019;Ueda et al, 2020;Yang et al, 2020b). Therefore, the present study utilized 16 microarray datasets for which the DEGs could be extracted from publicly available datasets and shortlisted 8 of them that shared the largest number of 3020 DEGs for WGCNA and other analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of non-canonical G4 motifs is different from that of canonical RNA sequences (Guo and Bartel, 2016;Yang et al, 2020). For example, cross-linking and immunoprecipitation (CLIP), one of the most used methods for identifying RNAs as protein binding targets from whole cellular RNA, often result in selective loss of most non-canonical G4 motifs.…”
Section: Dedicated Methods Of G4-rnamentioning
confidence: 99%
“…Although this might be true for mammalian cells, the same effect was not observed in Arabidopsis (Jackowiak et al, 2017). Recently, G-quadruplex structures were detected in Arabidopsis and rice, with different folding predictions in both species and developmental stages, suggesting that this structures could be spatio-temporal specific (Yang et al, 2020). The 4 Gs present in Arabidopsis tRNA-half (Ala) are not essential to affect protein synthesis.…”
Section: Signaling Molecules and Translation Modulatorsmentioning
confidence: 98%